Accurate estimation of choriocapillaris flow deficits beyond normal intercapillary spacing with swept source OCT angiography - Zhang, Qinqin; Shi, Yingying; Zhou, Hao; Gregori, Giovanni; Chu, Zhongdi; Zheng, Fang; Motulsky, Elie H.; Sisternes, Luis de; Durbin, Mary; Rosenfeld, Philip J.; Wang, Ruikang K. (Quantitative Imaging in Medicine and Surgery, 2018)
Background: To estimate choriocapillaris flow deficits beyond normal intercapillary distance with swept source optical coherence tomography angiography (SS-OCTA). Methods: Subjects were enrolled and repeated SS-OCTA scans were performed using the 3 mm × 3 mm scan pattern. Blood flow was identified using the complex optical microangiography (OMAGc) algorithm. The choriocapillaris (CC) was defined as a 20 µm slab of the flow volume beneath the outer boundary of Bruch’s membrane (BM) and was compensated with the corresponding structural image for flow deficits measurement. Flow deficits were segmented based on one mean standard deviation from a normal database. A histogram based thresholding method was developed to remove small flow deficits that were determined by examining intercapillary spacing within normal CC networks. A registration method based on affine and B-spline transformation was utilized for the CC angiogram averaging. Four repeated scans were averaged, and results were compared with and without removal of small flow deficits after averaging a different number of scans (N=1, group 1; N=2, group 2; N=3, group 3 and N=4, group 4). Results: Seven normal subjects were enrolled. Intercapillary distance was found to be 24 µm for the CC networks under OCTA, which was used as the threshold to exclude small flow deficits for CC quantification. After averaging, significant reduction in background noise and improvement in continuity of blood vessel networks were observed both on retinal and choriocapillaris angiograms. Flow deficit percentages of the choriocapillaris were significantly reduced with averaging (group 1 vs. group 2: P